Perceived Oral Hygiene Status, Dental Service Utilization and Treatment Needs of Medical and Nursing Students at A Tertiary Institution in Nigeria: a Cross-sectional Study (Nigerian Dental Journal, 2025)
ObjectiveTo evaluate the perceived oral hygiene status, dental service utilization, and treatment needs of medical and nursing students at a tertiary institution in Nigeria.MethodsThis descriptive cross-sectional study was conducted among clinical medical and nursing students at the University of Port Harcourt. A semi-structured questionnaire was used to collect data on socio-demographic variables, perceived self-rated oral hygiene status, dental service utilization, and treatment needs. Statistical analysis was performed using SPSS version 25.0 (IBM SPSS Inc., Chicago, Illinois). Descriptive statistics were computed, and associations were tested using the chi-square test and Fisher's exact test where appropriate. A p-value < 0.05 was considered statistically significant.ResultsA total of 155 participants were included, with 85 (54.8%) being clinical medical students and 70 (45.2%) being clinical nursing students. Only 6 (3.9%) of the medical students and 5 (3.2%) of the nursing students rated their oral hygiene as excellent. Dental clinic visits in the last 12 months were significantly higher among nursing students (50.0%) compared to medical students (32.9%), p = 0.031. More nursing students (67.1%) than medical students (49.4%) reported needing further dental treatment (p = 0.034). The most commonly required treatment was scaling and polishing.Conclusion The overall perception of oral hygiene among participants was suboptimal. While half of the nursing students visited the dental clinic in the past year, a significant proportion of medical students did not. There is a need for improved oral health awareness and preventive dental care promotion among medical and nursing students.
Keywords: Perceived oral hygiene; Utilization; Treatment needs; Medical; Nursing students